Research Bac Ha dog semen frozen in liquid nitrogen -196oC - Thu, Do Van; Binh, Doan Viet; Khoi, Tran Xuan; Hue, Le Thi (Academia Journal of Biology, 2017)
Bac Ha dog is a endemic breed living in Bac Ha district of Lao Cai Province. They have many good characteristics to train the dogs. But now due to spontaneous breeding and management is not tight, Bac Ha dog hybrid is pretty much, they lose those characteristics. Research dog frozen semen Bac Ha is an effective solution to conserve genetic resources and developing precious dogs. In this experiment, 50 semen samples from 6 Bac Ha dog were took which is bred naturally. The semen sample had motility rate higher than 70%, living rate higher than 85% and abnormality rate lower than 20% is used in the frozen testing. These factors influence the quality of frozen semen were surveyed after the experiment: the effect of freezing extender; effects of cryoprotectants glycerol and ethylene glycol; the influence of semen diluted incubation period before freezing; the effects of freezing temperatures. Results showed that frozen semen in frozen extender1 has motility rate after freezing (41.01%) significantly higher (p <0.05) compared with frozen semen in extender2 (34.17%). Proportion of living sperm after freezing by extender1 (66.95%) significantly higher (p <0.05) compared with extender2 (57.93%). Motility of sperm frozen in case additional glycerol (42.65%) significantly higher (p <0.05) compared with the additional ethylene glycol (35.15%). Additional glycerol into the extender at concentrations of 6.5% or 7.0% have a positive impact on the viability of frozen sperm. Additional extenders glycerol in time after 2 hours of sperm incubation at 4oC positive impact on sperm quality after freezing. The minimum incubation period before dilution frozen semen is 6 hours. Semen diluted incubation time 6 or 8 hours before freezing has motility rate after freezing well. Lower temperatures of the straws down to -165oC before dip straws into liquid nitrogen at -196oC have a better impact on sperm quality after freezing than lower to -130oC.   Citation: Do Van Thu, Doan Viet Binh, Tran Xuan Khoi, Le Thi Hue, 2017. Research Bac Ha dog semen frozen in liquid nitrogen -196oC. Tap chi Sinh hoc, 39(2): 249-257. DOI: 10.15625/0866-7160/v39n2.8867. *Corresponding author: dovanthu_ibt@yahoo.com Received 16 November 2016, accepted 20 June 2017